Future career as obstetrician and gynaecologist: final year medical students perspective point of view - Abd. Wahab, Noraziana; Sidek, Ayu Aszliana; Mat Desa, Norliza; Abdullah, Suhaiza; Awang, Mokhtar (Faculty of Medicine, International Islamic University Malaysia, 2013)

(untitled)
Obstetrics and gynaecology is unique as all patients are female and involves persons awra’ or private part. It is a fardhu kifayah for muslim doctors to undertake this specialty. Thus, we should encourage our students, especially female to enter this specialty and find ways to keep them interested in this field. To determine the medical students' career decision regarding obstetrics and gynaecology and to identify factors related to this decision making. Male to female respondents were also compared. The gender preferences when selecting their obstetrician and gynaecologist doctor were also analyzed. The study was conducted among final year medical students. They were asked to answer the questionnaires to assess their decision and justifications and also other preferences as their future career.100 final year medical students completed the survey, comprising of fifty-two females and forty-eight males. Out of fifty-two female students, twenty-two (42.3%) choose to further their study in obstetrics and gynaecology while another thirty students choose other specialty. 50.0 % feels that female patient should be treated by female doctor as fardhu kifayah and 36.4% feel that this career is interesting and challenging. Only two out of forty-eight male students (4.2%) choose to further their study in obstetrics and gynaecology. 95% of students preferred female doctors to treat them (or their spouse). Only 24% of students want to further their study in obstetrics and gynaecology. Female students were more likely to choose this career compared to male. Majority of students select their Obstetrician and gynaecologist based solely on gender. Religious reason was the strongest factor rated by students as why they choose this specialty.